THE INFLUENCE OF MOBILE BANKING SERVICE QUALITY ON CUSTOMER SATISFACTION OF INDONESIAN SHARIA BANK (CASE STUDY: ASN UIN IMAM BONJOL PADANG) - AMNAH SARI; YENTI AFRIDA; NILA MARDIAH (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2022)
This research is a type of quantitative research that aims to determine the effect of the quality of mobile banking Bank Syariah Indonesia on customer satisfaction. The data used in this study is primary data obtained directly from the answers of 88 respondents who are ASN UIN Imam Bonjol Padang as customers of mobile banking BSI The analytical method used is a simple linear regression analysis method. Based on the results of the study, it is known that the variable quality of mobile banking has an influence on customer satisfaction from the results of hypothesis testing or t-test, a significance value of 0.000 < than 0.05. From the simple linear regression equation, the X regression coefficient is 0.518 which states that if the quality of mobile banking services (X) increases by one unit, then customer satisfaction (Y) will increase by 0.518 or 51.8%. In the R-Square coefficient of determination the effect of mobile banking (X) on customer satisfaction (Y) is 0.713=71.3% and the remaining 28.7% is influenced by factors other than service quality that are not included in this study.